Strategic analysis of Mercedes Benz AG : The electric vehicles' EQ category - Galetti, Michela (2022)
Abstract: The subject of the bachelor’s thesis is Mercedes-Benz, a German luxury automotive brand. The purpose of the bachelor’s thesis is to conduct the strategic analysis of this company with a particular focus on the electric vehicles’ EQ category, given the recent commitment of the European Union to reduce CO2 emissions thus making the EU climate neutral by 2050. This policy is commonly known as European Green deal. The reason why the author would mainly concentrate my thesis on such issue, is because the automotive industry will be deeply affected by such policy in the future, since the latter have already shifted its production towards sustainable mobility solutions. In particular, the category of luxury brands will be affected the most by such change, given that these vehicles pollute the environment the most. Strategic analysis is defined as a process aimed at collecting relevant data which help the company’s board of directors to decide on several priorities and goals, to achieve a long-term strategy for the business itself. By doing so, the company can understand its environment and draw up a strategic plan accordingly. The data need to be both quantitative and qualitative, as they relate to the internal resources and the external environment. Strategic analysis will help the company to have a better understanding of the areas where further improvement might be needed and what is already in place. The bachelor’s thesis is divided into two main parts; the theoretical one, in which the tools used to conduct the strategic analysis will be elaborated. And the practical one, which is utilizing the tools and methods mentioned beforehand.